5018 Sayılı Kanun Üzerine Bir Değerlendirme - Kanca, Osman Cenk (Muş Alparslan Üniversitesi, 2017)
As well as the developments in the World economies, the national conjuncture in 1980 and 90ies has required process of fiscal structural reform that Turkey needs. In this content, in Turkey, important regulations were made referring to management, finance and controlling with Public Finance Management and Control Law of item 5018. It can be said that the most important reforms, which came into force with Public Finance Management and Control Law of item 5018, are changing the kinds of budget and content, the period of expenditure, founding the balance between authority and responsibility in expenditure period, and forming a sound accountability mechanism. In this study,  the reforms, which came into force to Turkish Budget System according to law of item 5018, are emphasized and then above-mentioned law is tried to be assessed from the point of legal, structural and budgeting aspects.

Dünya ekonomilerindeki gelişmelerin yanı sıra 80’li ve 90’lı yıllardaki ulusal konjonktür, Türkiye’nin ihtiyaç duyduğu mali yapısal reform sürecini gerekli kılmıştır. Bu bağlamda, Türkiye’de 5018 sayılı Kamu Mali Yönetimi ve Kontrol Kanunu ile yönetim, maliye ve denetime ilişkin önemli düzenlemelere gidilmiştir. 5018 sayılı Kamu Mali Yönetimi ve Kontrol Kanunu’nun kamu mali sistemine getirdiği en önemli yenilikler; bütçe türleri ve kapsamının değiştirilmesi, harcama süreci, harcama sürecinde yetki sorumluluk dengesinin kurulması ve sağlıklı hesap verebilme mekanizmasının oluşturulması olduğu söylenebilir. Bu çalışmada; 5018 sayılı KMYK’nın Türk Bütçe Sistemine getirdiği yenilikler üzerinde durulmuş daha sonra anılan kanun yasal, yapısal ve bütçeleme açısından değerlendirilmeye çalışılmıştır.
An Evaluation on the Law Number 5018
anemon
Keywords: Public Finance Management and Control Law 5018; Turkish Financial System; Financial Reform; 5018 Sayılı Kamu Mali Yönetim ve Kontrol Kanunu; Türk Bütçe Sistemi; Mali Reform